The selection and development of tribological coating - Kharlamov, Y.; Lopata, L.; Brusilo, Y.; Holovashuk, M. (Problems of Tribology, 2021)
The strategy and methodology for selecting of optimal surface treatment for a given tribological application are the main objectives of study. The classification of main methods of coating processes and surface modification is given. The scheme of development of operation technology of surface treatment and coating deposition is proposed. The main initial data: the structure of tribological system (TrS); individual properties of TrS parts; lubricant properties; method of lubrication of TrS parts; properties of surrounding environment; external influences on TrS; technological limitations on TrS parts treatment; managerial and economical limitations. The selection of surface technology method is including the next successive steps: the preliminary analysis of TrS part interaction; development of models of friction and wear process of TrS parts; the choice of rational values of parameters of surface layers of TrS parts; the choice of rational composition and structure parameters of surface layers of TrS parts; the choice of rational technological route and methods of surface treatment of TrS parts; the experimental examination of surface strengthened materials and TrS and correction of surface treatment technology